2010
DOI: 10.1007/s11999-010-1386-5
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Morphologic Differences in Subtypes of High Developmental Dislocation of the Hip

Abstract: Background Previous studies show the shape of the femur in developmental dislocation of the hip (DDH) becomes more abnormal with increasing subluxation. Two kinds of high dislocations associated with DDH have been observed in clinical practice, one with (Type C1) and one without (Type C2) a false acetabulum. The presence or absence of a false acetabulum in high dislocated hips is associated with different loading patterns and could influence the development and shape of the proximal femur. Questions/purposes W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 15 publications
(28 reference statements)
0
37
0
2
Order By: Relevance
“…In Hartofilakidis' study, three dislocations occurred out of 30 hips in the no false acetabulum group (10%) while there were zero out of 49 hips in the false acetabulum group (0%). This can be explained by the fact hips without false acetabulum have a worse soft tissue condition and abductor muscle strength because of a high‐riding femoral head in the gluteal musculature, and it has a more abnormal proximal femur shape caused by the lower mechanical loads.…”
Section: Discussionmentioning
confidence: 96%
“…In Hartofilakidis' study, three dislocations occurred out of 30 hips in the no false acetabulum group (10%) while there were zero out of 49 hips in the false acetabulum group (0%). This can be explained by the fact hips without false acetabulum have a worse soft tissue condition and abductor muscle strength because of a high‐riding femoral head in the gluteal musculature, and it has a more abnormal proximal femur shape caused by the lower mechanical loads.…”
Section: Discussionmentioning
confidence: 96%
“…Assim, são pertinentes novas análises de como o padrão geométrico pode interferir em patologias do fêmur. [7][8][9][10] Segundo estatísticas americanas, mais de 250 mil fraturas de quadril ocorrem a cada ano e esse número deverá estar duplicado em aproximadamente 30 anos. 4 O tratamento da maioria das fraturas de fêmur é cirúrgico.…”
Section: Discussionunclassified
“…Survivorship was lower in hips without a pseudoacetabulum (p = 0.001). Although there are no other studies in the literature comparing results of THA in high dislocation subtypes, this outcome seems reasonable, because C2 type hips have more affected morphology compared with C1 type hips that may result in a higher rate of failure [13,21]. Cox regression analysis, after adjustment for confounding factors, also showed statistically significantly worse survivorship in the C2 subtype (p = 0.021) and, after adjustment for possible predictive factors, we found a statistically significant relationship of high dislocation subtype (p = 0.018) and trochanteric union (p = 0.005) with survival of THAs.…”
Section: Discussionmentioning
confidence: 99%
“…We have recognized two subtypes of high dislocation of the hip on the basis of the presence (C1 hips) or absence of a false acetabulum (C2 hips) [10]. Xu et al [21] found that the presence or absence of false acetabulum in high dislocated hips is associated with different loading patterns and that this could influence the development and shape of the proximal femur.…”
Section: Introductionmentioning
confidence: 99%